Clinical outcomes of endoscopic ultrasound-guided hepaticogastrostomy-based internal drainage for unresectable malignant hilar biliary obstruction: a comprehensive evaluation with malignant distal biliary obstruction - Daiki Yamashige; Susumu Hijioka; Yoshikuni Nagashio; Shota Harai; Yasuhiro Komori; Aoi Kita; Masaru Kuwada; Soma Fukuda; Shin Yagi; Kohei Okamoto; Daiki Agarie; Shunsuke Sugawara; et al. (Therapeutic Advances in Gastroenterology, 2025)
Background: Endoscopic retrograde cholangiopancreatography (ERCP) may not provide adequate drainage for patients with malignant hilar biliary obstruction (MHBO). Endoscopic ultrasound-guided hepaticogastrostomy (EUS-HGS) is a salvage method for malignant distal biliary obstruction (MDBO); however, its effectiveness for MHBO remains unclear. Objectives: We aimed to evaluate the short- and long-term outcomes of EUS-HGS for MHBO. Design: This was a single-center retrospective cohort study. Methods: Unresectable patients who underwent initial EUS-HGS because of ERCP failure were recruited. Distal biliary stenosis or Bismuth types I and II–IV were defined as MDBO and MHBO, respectively. We defined EUS-HGS for MDBO as the control and analyzed the outcomes for MHBO. Results: The MDBO group ( n  = 208) was treated using EUS-HGS alone. In the MHBO group ( n  = 63), EUS-HGS alone (unilateral drainage, n  = 26), EUS-HGS with bridging (EUS-HGSB, bilateral drainage, n  = 21), and ERCP + EUS-HGS (bilateral drainage, n  = 16) were performed. In EUS-HGS (MDBO), EUS-HGS (MHBO), EUS-HGSB, and ERCP + EUS-HGS, the technical success rates were 98.6%, 96.3%, 95.5%, and 94.1%; clinical success rates were 88.5%, 76.9%, 85.7%, and 75.0%; adverse event rates were 19.7%, 15.4%, 9.5%, and 25.0%; and non-recurrent biliary obstruction (RBO) rates at 180 days were 45.5%, 19.8%, 61.9%, and 68.4%, respectively. In multivariate analysis of the MHBO group, EUS-HGSB tended to have a lower risk of RBO (adjusted hazard ratio (aHR), 0.39; p  = 0.09), and ERCP + EUS-HGS showed a significantly lower risk (aHR, 0.25; p  = 0.03) compared to EUS-HGS alone (unilateral drainage). Conclusion: ERCP + EUS-HGS followed by EUS-HGSB, providing bilateral drainage, can offer preferred palliation for MHBO. These drainages may serve as potential salvage options in the management of MHBO.